Geoambientes, geoarqueologia e cenários de mudanças climáticas na Ilha de Marajó, Amazônia Brasileira - Renata Jordan Henriques (2022)
Marajó Island, located at the mouth of the Amazon River in the state of Pará, is part of one of the largest river-estuarine archipelagos on the planet. Its more than 30,000 thousand km² safeguard the legacies of its human and environmental evolution during the Holocene, which culminated in multiple geodiversity in its landscape. The main aims of this research were to investigate the multiple geoenvironmental and anthropogenic legacies of the island and their meanings for the evolution of the Marajoara landscape, in addition to making it possible to predict future scenarios for the region. As a methodology, 20 soil profiles were sampled and described in December 2018, and their physical and chemical laboratory analyses were carried out; (ii) dated charcoal and organic matter samples by 14C isotope; (iii) performed procedures by remote sensor, such as recognition of surface spectral signatures, compartmentalization of geoenvironments and topographic sections. The main results of this work were: (i) the identification and characterization of 21 main geoenvironments that form the Marajó island's landscapes; (ii) the recognition of different Terras Pretas de Índio, with and without ceramics, which refer to historical processes of occupation and agriculture; (iii) mapping the zone occurrence of saline soils and respective spectral responses; (iv) indicators in soils and vegetation from a warmer and drier Lower Holocene to wet and hottest temperatures in the Late Holocene; (v) the identification of climate change vulnerabilities and the rise of the oceans water level at the global coasts, beyond recognizing erosion trends in the coastal region of Marajó Island; (vi) the presentation of actions to mitigate possible human, geoarchaeological and environmental impacts in relation to climate change. As expectations for the continuation of the research later the thesis conclusion: (i) the improvement and dissemination of discussions on saline soils, their mineralogy and geochemistry; (ii) advances in discussions of future climate vulnerabilities in the region; (iii) the expansion of the investigation of a microscopic universe, through the use of thin sections of soils and shells and grains morphoscopy; (iii) in addition, a synthesis of the project through a book, or other visual resources, to facilitate disclosures and contributions to knowledge about the bays of Brazil, beyond Marajó estuary.